INSTRUCTIONAL LEADERSHIP: THE ROLE OF SCHOOL PRINCIPALS IN ELEVATING TEACHER PERFORMANCE IN SMAN 13 BANJARMASIN - SA, KHOIROTUN NISA; ASLAMIAH, ASLAMIAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research investigates the role of instructional leadership in enhancing teacher professionalism at SMAN 13 Banjarmasin, a prominent high school in Indonesia. Amid significant educational transformations driven by the Ministry of Education and Culture's Strategic Plan (2015-2019), the study emphasizes the necessity of effective leadership in improving academic standards and student outcomes. Utilizing a descriptive qualitative approach, data were collected through interviews, observations, and document reviews to explore the dynamics between instructional leadership and teacher development. Findings reveal that the principal's proactive strategies, including fostering collaboration among teachers, implementing professional development programs, and adapting to challenges such as the shift to online learning during the pandemic, significantly contribute to enhancing educational quality. However, challenges persist, including issues related to teacher discipline and administrative documentation. The study concludes that effective instructional leadership is crucial for continuous improvement in educational quality, advocating for ongoing research and development in this area to meet the demands of the 21st century. By focusing on both teacher professionalism and student achievement, the principal at SMAN 13 Banjarmasin exemplifies the vital role of leadership in fostering a supportive and effective learning environment.